2019
DOI: 10.1111/mec.15083
|View full text |Cite
|
Sign up to set email alerts
|

Population assignment reveals low migratory connectivity in a weakly structured songbird

Abstract: Understanding migratory connectivity is essential for determining the drivers behind population dynamics and for implementing effective conservation strategies for migratory species. Genetic markers provide a means to describe migratory connectivity; however, they can be uninformative for species with weak population genetic structure, which has limited their application. Here, we demonstrated a genomic approach to describing migratory connectivity in the prothonotary warbler, Protonotaria citrea, a Neotropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…Genetically diverged candidate loci contain higher information content, allowing greater assignment accuracy than would be possible using an equal or greater number of neutral loci. For example, Freamo et al (2011) achieved 85% assignment accuracy when using 14 candidate outlier loci compared to 75% assignment accuracy when using 67 neutral loci in salmon, and studies in other systems have achieved equal success using many more markers (Benestan et al, 2015; DeSaix et al, 2019; Rannala & Mountain, 1997). The 10 candidate outlier loci available for summer flounder were differentiated across geography, but only weakly so, which resulted in low power to assign individuals to populations of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically diverged candidate loci contain higher information content, allowing greater assignment accuracy than would be possible using an equal or greater number of neutral loci. For example, Freamo et al (2011) achieved 85% assignment accuracy when using 14 candidate outlier loci compared to 75% assignment accuracy when using 67 neutral loci in salmon, and studies in other systems have achieved equal success using many more markers (Benestan et al, 2015; DeSaix et al, 2019; Rannala & Mountain, 1997). The 10 candidate outlier loci available for summer flounder were differentiated across geography, but only weakly so, which resulted in low power to assign individuals to populations of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Low genetic differentiation at neutral markers has limited efficacy for population assignment because of ongoing gene flow. However, candidate outlier loci, or gene‐associated markers, that arise due to divergent environmental selection are promising for population assignment because of their elevated differentiation compared to neutral markers (Benestan et al, 2015; DeSaix et al, 2019; Freamo et al, 2011; Nielsen et al, 2009, 2012). Genetically diverged candidate loci contain higher information content, allowing greater assignment accuracy than would be possible using an equal or greater number of neutral loci.…”
Section: Discussionmentioning
confidence: 99%
“…As body size is strongly related to important traits such as thermoregulatory (especially at such early post‐embryonic stages) and migratory ability, it would seem likely that there is at least some genetic basis for these patterns. However, a recent study of the population genomics of prothonotary warblers found little latitudinal population structure (but greater longitudinal variation, possibly related to geographic isolation between migratory pathways; DeSaix et al., 2019). This genomic work, however, was not designed to detect genetic differences related to body mass variation.…”
Section: Discussionmentioning
confidence: 99%
“…Prothonotary warblers have an incubation period of 11–14 days, fledging occurs 9–11 days following hatching (Petit, 1999), and they can produce up to three broods in a season. Recent studies of geographic variation in the species (on the breeding grounds) have identified weak longitudinal genetic population structure (DeSaix et al., 2019) and variation in color and sexual signaling (Slevin, Bulluck, Matthews, & Boves, 2019). During the non‐breeding season, the bulk of the global population appears to winter in a relatively small area in Colombia and Panama (Reese et al., 2019; Tonra et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation